Modeling the growth of Bacillus cereus in Napa cabbage (Brassica rapa subsp. pekinensis) across different sea salt concentrations - Eun Bi Jeon; Sung-Hee Park; Shin Young Park (Applied Food Research)
Bacillus cereus is common in nature and can contaminate food through soil and air. Root vegetables like Napa cabbage are especially prone to soil contamination. B. cereus toxins are mainly linked to ready-to-eat foods, such as raw napa cabbage, which poses a risk when consumed salted. This study proposes growth models for B. cereus growing on Napa cabbage as a function of sea salt concentrations (4–14 %). Samples were stored at 10 °C and analyzed at intervals from 2 to 120 h to determine bacterial growth rates at different salt concentrations. At these sea salt concentrations, the primary models fit well (R2 = 0.98) with the Baranyi model, using a polynomial model to obtain lag time (LT) and specific growth rate (SGR). However, as sea salt concentration increased, the growth of B. cereus decreased. Specifically, no B. cereus growth was observed at concentrations of 12 and 14 %. The LT values were 1.87, 2.87, and 6.04 h, and the SGR values were 0.21, 0.17, and 0.09 log CFU/h at sea salt concentrations of 4, 8, and 10 %, respectively. The suitability of the secondary models for LT and SGR was verified using the mean square error (MSE; <0.01, internal validation, <0.01), bias factor (Bf: 1.043–1.214 internal validation, 1.046–1.086 external validation), and accuracy factor (Af; 1.136–1.113 internal validation, 1.147–1.085 external validation). Ultimately, these models can be applied to improve the safety of various cabbage-based products (e.g., Kimchi).